1.rozwiąż równania
a)2(x-3)-(3x-1)=5
b)-(x+1)-2(1-x)=-4
c)3(x-2)+2(4-x)=6
d)-2(1-x)+3(2x+1)=-7
e)(x+3)-(2x-1)=1
f)-3(2-x)-2(1-3x)=10
2.rozwiąż równania
a)2(x+3)-(5-x)+2=3(x-1)
b)3(x-4)-2(3-2x)=-(3x-1)-(1-x)
c)2x-(x+4)-1=2-3(1-x)+3x
d)1-2(x-3)-(3x+5)=-x-(2x-1)+3
e)(x+2)+(x-3)-(4-x)=-(2x-5)-(3-x)+(2x-4)


z góry dziękuje proszę o dokładne rozwiązanie dziękuje

3

Odpowiedzi

2010-04-09T17:30:26+02:00
A)2x-6+3x-1=5
5x=5+6+1
5x=12/:5
x=2,4
b)-(x+1)-2(1-x)=-4
-x+1-2+2x=4
x=5
c)3(x-2)+2(4-x)=6
3x-6+8-2x=6
x=6+6-8
x=4

2010-04-09T17:33:09+02:00
A)2(x-3)-(3x-1)=5
2x-6-3x+1=5
2x-6-3x+1=5
2x-3x=5-1+6
x=10

b)-(x+1)-2(1-x)=-4
-x-1-2+2x=-4
x=-4+3
x=-1

c)3(x-2)+2(4-x)=6
3x-6+8-2x=6
3x-2x=6+6-8
x=4

d)-2(1-x)+3(2x+1)=-7
-2+2x+6x+3=-7
8x=-7-3+2
8x=-8
x=-1

e)(x+3)-(2x-1)=1
x+3-2x+1=1
-x=1-1-3
-x=-3
x=3

f)-3(2-x)-2(1-3x)=10
-6+3x-2+6x=10
9x=10+6+2
9x=18
x=2

2.
a)2(x+3)-(5-x)+2=3(x-1)
2x+6-5+x+2=3x-3
2x+x-3x=-3-6+5-2
0=-11+6
0=-6 roznanie sprzeczne


b) 3(x-4)-2(3-2x)=-(3x-1)-(1-x)
3x-12-6+4x=-3x+1-1+x
3x+4x+3x-x=1-1+6+12
14x=16
x=16/16 =1 i 2/14=1 i 1/7

c)2x-(x+4)-1=2-3(1-x)+3x
2x-x-4-1=2-3+3x+3x
2x-x-3x-3x=2-3+4+1
-5x=4
x=-4/5

d)1-2(x-3)-(3x+5)=-x-(2x-1)+3
1-2x-+6-3x-5=-x-2x+1+3
-2x-3x+x+2x=1+3+5-6-1
-2x=1
x=-1/2


e)(x+2)+(x-3)-(4-x)=-(2x-5)-(3-x)+(2x-4)
x+2+x-3-4+x=-2x+5-3+x+2x-4
x+x+x+2x-x-2x=5-3-4-2+3+4
-2x=3
x=-3/2
x= - 1 i 1/2
2010-04-09T17:35:10+02:00
A)2(x-3)-(3x-1)=5
2x-6-3x+1=5
-x=12
x=-12

b)-(x+1)-2(1-x)=-4
-x-1-2+2x=-4
x=-1

c)3(x-2)+2(4-x)=6
3x-6+8-2x=6
x=-8

d)-2(1-x)+3(2x+1)=-7
-2+2x+6x+3=-7
8x=-2
x=-4

e)(x+3)-(2x-1)=1
x+3-2x+1=1
3x=-3
x=-1

f)-3(2-x)-2(1-3x)=10
-6+3x-2+6x=10
9x=18
x=2

2.rozwiąż równania
a)2(x+3)-(5-x)+2=3(x-1)
2x+6-5+x+2=3x-3
0=-2

b)3(x-4)-2(3-2x)=-(3x-1)-(1-x)
3x-12-6+4x=-3x+1-1+x
9x=18
x=2

c)2x-(x+4)-1=2-3(1-x)+3x
2x-x-4+1=2-3+x+3x
2x=4
x=2

d)1-2(x-3)-(3x+5)=-x-(2x-1)+3
1-2x+6-3x-5=-x-2x+1+3
-2x=-8
x=4

e)(x+2)+(x-3)-(4-x)=-(2x-5)-(3-x)+(2x-4)
x+2+x-3-4+x=-2x+5-3+x+2x-4
x=3